DILMA PRESIDENTA A REPERCUSSÃO DA COMUNICAÇÃO POLÍTICA PARA VIABILIZAR A ELEIÇÃO DA PRIMEIRA MULHER A GOVERNAR O BRASIL PELA ÓPTICA DAS REVISTAS VEJA E CARTACAPITAL - Iwanikow, Margarete Salles (2013)
This dissertation focuses on the impact of political communication in the press coverage during the pre-candidature of Dilma Vana Rousseff for president of Brazil. The objective is to verify the political marketing strategies used to promote the name of the pre-candidate, as depicted by the magazines Veja and CartaCapital between March of 2008 and April of 2010, period that preceded the official nomination of the president Luiz Inácio Lula da Silva s successor. To develop the dissertation some concepts have been discussed, such as: political communication, electoral and political marketing, gender issues in politics and in the Brazilian society, and the female journey in the fight for equal rights that transformed the social imagery in relation to the women s role. Subjects such journalism and political cover in Brazil and a concise overview about political trajectory post-dictatorship in Brazil have also been considered besides the biographic profile of Dilma Rousseff. The importance of this research is in verifying how the pre-candidature of a woman to the highest public position in Brazil has echoed in the press, considering the difficulties and challenges of the female fight in the Brazilian politics. It is a quantitative and qualitative analysis with the use of content analysis, according to Laurence Bardin, that includes quantitative and qualitative perspectives. Through on the research it has been verified that the gender issue was one of the factors that positively influenced the election and, mainly, that the repercussion was positive to the political marketing intentions to promote the candidature of Dilma Rousseff to presidential succession.